ยุทธศาสตร์การเสริมสร้างความรู้ ความตระหนักและพฤติกรรมใน การใช้สารเคมีกำจัดศัตรูพืชของครัวเรือนเกษตรกรผู้ปลูกยาสูบ : กรณีศึกษาบ้านนากาง เมืองคูนคำ แขวงคำม่วน สาธารณรัฐประชาธิปไตยประชาชนลาว - ตุนาลม, อุไรพร (Journal of Graduate School Sakon Nakhon Rajabhat University, 2017)
ยุทธศาสตร์การเสริมสร้างความรู้ ความตระหนักและพฤติกรรมในการใช้สารเคมีกำจัดศัตรูพืชของครัวเรือนเกษตรกรผู้ปลูกยาสูบ : กรณีศึกษาบ้านนากาง เมืองคูนคำ แขวงคำม่วน สาธารณรัฐประชาธิปไตยประชาชนลาว STRATEGY TO ENHANCE KNOWLEDGE AWARENESS AND BAHAVIOR IN USING PLANT CHEMICAL OF FARMER-HOUSEHOLDS : THE CASE STUDY OF NAKANG VILLAGE, KHOUNKHAM DISTRICT, KHAMMOUANE PROVINCE, LAO PEOPLE’S DEMOCRATIC REPUBLIC บทคัดย่อ การวิจัยครั้งนี้มีจุดมุ่งหมายเพื่อ 1) ศึกษาสภาพปัจจุบัน ความต้องการและแนวทางการเสริมสร้างความรู้ ความตระหนักและพฤติกรรมในการใช้สารเคมีกำจัดศัตรูพืชของครัวเรือนเกษตรกรผู้ปลูกยาสูบ 2) สร้างยุทธศาสตร์การเสริมสร้างความรู้ ความตระหนักและพฤติกรรมในการใช้สารเคมีกำจัดศัตรูพืชของครัวเรือนเกษตรกรผู้ปลูกยาสูบ และ 3) ศึกษาผลการใช้ยุทธศาสตร์การเสริมสร้างความรู้ ความตระหนักและพฤติกรรมในการใช้สารเคมีกำจัดศัตรูพืชของครัวเรือนเกษตรกรผู้ปลูกยาสูบ กลุ่มเป้าหมายในการวิจัย คือ เกษตรกรผู้ปลูกยาสูบและเยาวชนบ้านนากาง เมืองคูนคำ แขวงคำม่วน สาธารณรัฐประชาธิปไตยประชาชนลาว จำนวน 40 คน ได้แก่ ผู้บริหารโรงเรียน ตัวแทนเกษตรกร นักวิชากร เยาวชน และ เกษตรกรผู้ปลูกยาสูบ เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูล ได้แก่ แบบสัมภาษณ์ แบบสอบถาม แบบทดสอบความรู้ แบบวัดความตระหนักและพฤติกรรมและแบบสอบถามความพึงพอใจ สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ค่าร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐานและการทดสอบที (t-test) ผลการวิจัยพบว่า 1. สภาพปัจจุบันและความต้องการของเยาวชนและเกษตรกร 1) ด้านความรู้เกี่ยวกับการใช้สารเคมีกำจัดศัตรูพืช พบว่า ทั้ง 2 กลุ่มประเมินตนเองว่ามีความรู้อยู่ในระดับปานกลาง เยาวชนต้องการพัฒนาความรู้อยู่ในระดับปานกลาง ส่วนเกษตรกรต้องการอยู่ในระดับมากที่สุด 2) ด้านความตระหนักการใช้สารเคมีกำจัดศัตรูพืช พบว่า เยาวชนมีความตระหนักอยู่ในระดับมาก ส่วนเกษตรกรอยู่ในระดับมากที่สุด และ 3) ด้านพฤติกรรมที่เหมาะสมในการใช้สารเคมีกำจัดศัตรูพืช พบว่า เยาวชนประเมินตนเองมีพฤติกรรมที่เหมาะสมอยู่ในระดับมากที่สุด ส่วนเกษตรกรอยู่ในระดับมาก สำหรับแนวทางการพัฒนา ผู้วิจัยเสนอไว้ในแบบสอบถาม พบว่า ทั้งเยาวชนและเกษตรกรเห็นด้วยอยู่ในระดับมากที่สุดทุกรายการ ยกเว้น รายการเกี่ยวกับการให้เกร็ดความรู้ผ่านเสียงตามสาย เกษตรกรเห็นด้วยอยู่ในระดับมาก 2. ยุทธศาสตร์ที่สร้างขึ้นมีเป้าหมายเพื่อเสริมสร้างความรู้ ความตระหนักและพฤติกรรมในการใช้สารเคมีกำจัดศัตรูพืชของครัวเรือนเกษตรกรผู้ปลูกยาสูบบ้านนากาง เมืองคูนคำ แขวงคำม่วน สาธารณรัฐประชาธิปไตยประชาชนลาว ประกอบด้วย การจัดอบรมเชิงปฏิบัติการ จัดทำคู่มือการใช้สารเคมีกำจัดศัตรูพืช สำหรับครัวเรือนเกษตรกรผู้ปลูกยาสูบเพื่อไว้ศึกษาด้วยตนเอง 3. ผลการทดลองใช้ยุทธศาสตร์ พบว่า 3.1 ทั้งเยาวชนและเกษตรกรมีความรู้ ความตระหนัก และพฤติกรรมการใช้สารเคมีกำจัดศัตรูพืชหลังการทดลองใช้ยุทธศาสตร์สูงกว่าก่อนการทดลองอย่างมีนัยสำคัญทางสถิติที่ระดับ .01 และ 3.2 ทั้งเยาวชนและเกษตรกรมีความพึงพอใจต่อการเข้าร่วมกิจกรรมโครงการอบรมเสริมสร้างความรู้และความตระหนักในการใช้สารเคมีกำจัดศัตรูพืชของเยาวชนและเกษตรกรผู้ปลูกยาสูบโดยรวมอยู่ในระดับมาก ABSTRACT The purposes of this study were: 1) to investigate the current state, need and way of enhancing knowledge, awareness and behavior of using chemical pesticides in the household of farmers who grew tobacco, 2) to create a strategy to enhance knowledge, awareness and behavior of using chemical pesticides among the tobacco farmers in their household, and 3) to examine the results of implementing the strategy to enhance knowledge, awareness and behavior of using chemical pesticides among the tobacco farmers. The target group was tobacco farmers and the youth in Ban Nakang village, Khounkham district, Khammouane province, Lao PDR totaling 40 people. The instruments used in data collection were an interview guide, a questionnaire, a test, and a form for measuring awareness. Statistics used in data analysis were percentage, mean, standard deviation and t-test. The findings of study were as follows: 1. The current state and need of the youth and farmers showed as follows: 1) In the aspect of knowledge about using chemical pesticides, both the youth and farmers assessed their own knowledge at moderate level; the youth needed to be developed in knowledge at moderate level, while the farmers needed at the highest level. 2) In the aspect of awareness in using chemical pesticides, the youth had their awareness at high level; while the farmers at the highest level. And 3) in the aspect of appropriate behavior in using chemical pesticides, the youth assessed themselves that they had their appropriate behavior at the highest level, while the farmers at high level. As for the ways to the development that were proposed in the questionnaire by this author, it was found that both the youth and farmers agreed with them for every particular at the highest level; except the particular in giving a bit of knowledge through the wire broadcasting, the farmers agreed with it at high level. 2. The created strategy aiming to enhance knowledge, awareness and behavior in using chemical pesticides by the household of tobacco farmers in Ban Nakang village, Khounkham district, Khammouane province, Lao PDR consisted of essential activities such as training both theoretical and practical, and producing a manual of using chemical pesticides for study by members of the household of tobacco farmers themselves. 3. The results of experiment in using the strategy showed the following: 3.1 Both the youth and farmers had significantly higher knowledge, awareness and behavior of using chemical pesticides after implementation of the strategy than those before the treatment at the .01 level. And 3.2 Both the youth and tobacco farmers were satisfied as a whole with their participation in activities of the training project for enhancing their knowledge and awareness of using chemical pesticides at high level.